The Role of Mammalian Reservoir Hosts in Tick-Borne Flavivirus Biology - Mlera, Luwanika; Bloom, Marshall E. (Frontiers in Cellular and Infection Microbiology, 2018)
Small-to-medium sized mammals and large animals are lucrative sources of blood meals for ixodid ticks that transmit life-threatening tick-borne flaviviruses (TBFVs). TBFVs have been isolated from various organs obtained from wild-caught Myodes and Apodemus species in Europe and Asia. Thus, these rodents are well-established reservoirs of TBFVs. Wild-caught Peromyscus species have demonstrated seropositivity against Powassan virus, the only TBFV known to circulate in North America, suggesting that they may play an important role in the biology of the virus in this geographic region. However, virus isolation from Peromyscus species is yet to be demonstrated. Wild-caught medium-sized mammals, such as woodchucks (Marmota monax) and skunks (Mephitis mephitis) have also demonstrated seropositivity against POWV, and virus was isolated from apparently healthy animals. Despite the well-established knowledge that small-to-medium sized animals are TBFV reservoirs, specific molecular biology addressing host-pathogen interactions remain poorly understood. Elucidating these interactions will be critical for gaining insight into the mechanism(s) of viral pathogenesis and/or resistance.